Advances in contrast-enhanced MR-angiography - Aschauer, Manuela Adelinde (Radiology and oncology (Ljubljana), 2002)
Introduction. Gadolinium(Gd)-enhanced three-dimensional (3D) magnetic resonance angiography (MRA) is a newer technique that provides high resolutiondata rapidly for depiction of both arteries and veins throughout thebody. Conclusions. Contrast-enhanced 3D MRA represents a milestone for non-invasive vascular imaging. While its clinical utility has already been established in many vascular territories, the continuos development of hard- and software, as well as of new contrast agents, will likely result in a further widening in the spectrum of indications. Delayed 3D acquisitions of the kidney, ureters and bladder can be performed routinely to demonstrate and characterise obstruction, delayed function, filling defects and masses. Some patients are not candidates for MRA because of pacemakers, some kind of stentsor immobilisation coils that cause considerable artifacts and obscure important structures. The resolution of CE-3D-MRA is lower compared with that of conventional angiography and visualisation of small peripheral arteries is limited.
Keywords: angiografija; Aorta; arterije; Contrast media; diagnostika; Gadolinij; Gadolinium; Kontrastna sredstva; Magnetic resonance imaging; Magnetna resonanca; ožilje; Periferne žile, bolezni; Peripheral vascular diseases; Pljučna arterija; Pulmonary artery; Veins; Vene